The Effect of Maggot Flour Substitution in Artificial Feed Formulations on the Growth and Survival of Snakehead (Channa striata) - Prananda, Muhammad Rizky; Haetami, Kiki; Suryana, Asep Agus Handaka; Herman, Roffi Grandiosa (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
The high price of fish meal is also a reason for alternatives and better protein sources. This research aims to substitute fish meal with maggot meal in feed for snakehead fish's growth rate and survival. The method used in this research is the experimental method of Completely Randomized Design (CRD), which consists of five treatments and three replications. The treatments used were (A) without the use of maggot flour (control), (B) 15% maggot flour substitution, (C) 30% maggot flour substitution, (D) 45% maggot flour substitution, (E) 60% maggot flour substitution, which was maintained for 50 days. The test fish used were snakehead fish with a 9-10 cm length and weighing 7-9 g. The container used is an aquarium with dimensions of 40x26x28 cm3 or a water volume of 15 L, in which five snakehead fish are placed in each aquarium. The amount of feed given is 5% of the fish biomass. The results obtained during the research showed that treatment E with the substitution of fishmeal for maggot meal at 60% of the feed resulted in the highest absolute length growth of 4.0 cm, the highest specific growth rate of 2.54%, and survival of 87%.